Courses for Kids
Free study material
Offline Centres
Last updated date: 05th Dec 2023
Total views: 382.8k
Views today: 6.82k
MVSAT Dec 2023

If $a\cos \theta -b\sin \theta =c$, show that $a\sin \theta +b\cos \theta =\pm \sqrt{{{a}^{2}}+{{b}^{2}}-{{c}^{2}}}$.

382.8k+ views
Hint: Square both sides of the given expression and use the trigonometric identities ${{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $and ${{\sin }^{2}}\theta =1-{{\cos }^{2}}\theta $ to obtain the square of the expression on LHS of the second expression. On rearrangement, the only expression that remains on the LHS is the square of $a\sin \theta +b\cos \theta $ and the RHS is an expression in a, b and c. Then find square roots on both sides to get the required result.

Complete step-by-step answer:
We are given the equation $a\cos \theta -b\sin \theta =c$. The first step in this case will be to square both sides. Thus, squaring both sides gives us

&{{\left( a\cos \theta -b\sin \theta \right)}^{2}}={{c}^{2}} \\
& \Rightarrow {{a}^{2}}{{\cos }^{2}}\theta +{{b}^{2}}{{\sin }^{2}}\theta -2ab\sin \theta \cos \theta ={{c}^{2}} \\

Now we know that ${{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $ and that ${{\sin }^{2}}\theta =1-{{\cos }^{2}}\theta $. We substitute these values in the squared expression to obtain
 &{{a}^{2}}\left(1-{{\sin }^{2}}\theta \right)+{{b}^{2}}\left( 1-{{\cos }^{2}}\theta \right)-2ab\sin \theta \cos \theta ={{c}^{2}} \\
 & \Rightarrow {{a}^{2}}+{{b}^{2}}-{{a}^{2}}{{\sin }^{2}}\theta -{{b}^{2}}{{\cos }^{2}}\theta -2ab\sin \theta \cos \theta ={{c}^{2}} \\
 & \Rightarrow {{a}^{2}}{{\sin }^{2}}\theta +{{b}^{2}}{{\cos }^{2}}\theta +2ab\sin \theta \cos \theta ={{a}^{2}}+{{b}^{2}}-{{c}^{2}}\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \quad \ldots \left( 1 \right) \\

Now, to consider the expression whose value has to be found, we square that expression to obtain
${{\left( a\sin \theta +b\cos \theta \right)}^{2}}={{a}^{2}}{{\sin }^{2}}\theta +{{b}^{2}}{{\cos }^{2}}\theta +2ab\sin \theta \cos \theta $
The expression on this equation’s RHS is the same as the expression on the LHS of equation (1). Hence, the value of ${{\left( a\sin \theta +b\cos \theta \right)}^{2}}={{a}^{2}}+{{b}^{2}}-{{c}^{2}}$.

Taking square roots on both sides of this equation, we obtain $a\sin \theta +b\cos \theta =\pm \sqrt{{{a}^{2}}+{{b}^{2}}-{{c}^{2}}}$, which is the required result.
Hence the result is proved.

Note: The fairly simple question seems difficult at first sight but the trick is to transform the expression in the question to the one whose value has to be found. To do this in questions involving $\sin $ and $\cos $ functions of the same angle $\theta $, the best way is to find the square on both sides and then use the identities of ${{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $ and ${{\sin }^{2}}\theta = 1-{{\cos}^{2}}\theta$.